Pengaruh Literasi Keuangan Terhadap Penggunaan Paylater Dengan Variabel Gaya Hidup Sebagai Variabel mediasi - Drajati, Dewi Prasetyan; Hanantijo, G.M. Djoko (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
Ampetitive prices during pandemic Covid- 19. E-commerce provided several ways to do payment such as bank transfer, credit card, e-wallet, cash on delivery, and paylater. Paylater was one of the most favorite used features because buyer could get the product and paid for it later. Paylater had increased transaction up to 91% in e- commerce. Paylater usage had to be controlled because there would be huge risk like big amount of debt if buyer didn’t pay the installments. Financial literacy and lifestyle were considered to be factors that could controlled the paylater feature usage. Inside this research there would be 384 respondents who work as employee at private companies at Jakarta. Based on the data calculation by using SmartPLS, financial literacy and lifestyle positively significant to influence paylater feature usage.